2022
DOI: 10.1021/acs.inorgchem.2c01667
|View full text |Cite
|
Sign up to set email alerts
|

Borylation in the Second Coordination Sphere of FeII Cyanido Complexes and Its Impact on Their Electronic Structures and Excited-State Dynamics

Abstract: Second coordination sphere interactions of cyanido complexes with hydrogen-bonding solvents and Lewis acids are known to influence their electronic structures, whereby the non-labile attachment of B­(C6F5)3 resulted in several particularly interesting new compounds lately. Here, we investigate the effects of borylation on the properties of two FeII cyanido complexes in a systematic manner by comparing five different compounds and using a range of experimental techniques. Electrochemical measurements indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…32 Borylation of the peripheral nitrogen atoms of the cyanido ligands presumably further strengthens the ligand field, 33 yet the detectable excited-state lifetime of 28 ps in [Fe(bpy)(BCF) 4 ] 2− (BCF = tris(pentafluorophenyl)) (Figure 3c) was attributed to an MC rather than an MLCT state. 34 Further MLCT excited- state tuning in iron(II) cyanido complexes is possible through variation of the α-diimine ligands. 35 N-Heterocyclic carbene (NHC) ligands emerged as better alternatives to polypyridines as far as long 3 MLCT lifetimes are concerned, largely owing due their stronger σ-donor properties.…”
Section: ■ Iron(ii) Compoundsmentioning
confidence: 99%
“…32 Borylation of the peripheral nitrogen atoms of the cyanido ligands presumably further strengthens the ligand field, 33 yet the detectable excited-state lifetime of 28 ps in [Fe(bpy)(BCF) 4 ] 2− (BCF = tris(pentafluorophenyl)) (Figure 3c) was attributed to an MC rather than an MLCT state. 34 Further MLCT excited- state tuning in iron(II) cyanido complexes is possible through variation of the α-diimine ligands. 35 N-Heterocyclic carbene (NHC) ligands emerged as better alternatives to polypyridines as far as long 3 MLCT lifetimes are concerned, largely owing due their stronger σ-donor properties.…”
Section: ■ Iron(ii) Compoundsmentioning
confidence: 99%
“…In solvents of high acceptor number (and therefore higher E MLCT ), the metalcentered states may become relatively lower in energy, leading to more rapid deactivation. 45 As E MLCT decreases (with lower AN), deactivation via MC states becomes less significant, but direct deactivation to the ground state increases in accordance with the energy gap law.…”
mentioning
confidence: 68%
“…[40][41][42] (This may be viewed as an intermolecular extension of covalent Lewis acid-cyano adducts which have been recently investigated. [43][44][45] ) The energies of the filled dπ and the empty d z 2 should therefore drop in acidic environments. The energy of the tetraimine π system is expected to stay relatively constant in contrast, 41 so E MLCT concomitantly increases (Chart 1), as observed experimentally.…”
mentioning
confidence: 99%
“…45,46 Most recently, Wenger et al provided a comprehensive study of the electronic structural properties of Fe(II) boronated cyanometallates as a function of the number of cyanide ligands. 47 Studies of cyanometallates have been driven by the promise of applications in magnetic materials involving single-molecule/ Prussian-Blue analogues and in electrode materials for solidstate batteries. 18,48−50 Of direct relevance to our research is the performance of reversible cyanometallates as electrolytes in redox flow batteries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, boronation also has similar effects on the spectroscopic and photophysical properties of heteroleptic iridium­(III) and copper­(I) diimine complexes. , Of interest is that BCF/BPh 3 adducts of heteroleptic rhenium­(I) diiminecarbonyls have shown promise as selective sensors for cyanide anions . Also, Wenger et al boronated heteroleptic ruthenium­(II) and iridium­(III) diimine complexes and demonstrated their high activity for energy transfer and photoredox catalysis. , Most recently, Wenger et al provided a comprehensive study of the electronic structural properties of Fe­(II) boronated cyanometallates as a function of the number of cyanide ligands …”
Section: Introductionmentioning
confidence: 99%